Wyznania starego czlowieka - Hertz, Aleksander (Londyn : Oficyna Poetow i Malarzy, 1979)
Autobiography of the Polish sociologist.
Keywords: Hertz, Aleksander; Sociologists -- Poland -- Biography; Poland -- Biography